Fundamental Differences Related to Laws Discussion According to al-Mardawiy in His Book al-Tahbir Syarh al-Tahrir | الفروق الأصولية المتعلقة بمباحث الأحكام عند المرداوي في كتابه التحبير شرح التحرير - Mustori Mustori; Rusli Hasbi (Al-Zahra : Journal for Islamic and Arabic Studies, 2021)
This study aims to explain furuq usuliyyah (fundamental differences) contained in the book al-Tahbeer Syarh al-Tahrir fi Ushul al-Fiqh by al-Imam 'Ala al-din al-Mardawy, by comparing it with the opinions of the fiqh proposal experts, and aim to apply it to fiqh law. The research method used by the author in this study is the inductive method, by conducting a search of the works in the field of Usul Fiqh and al-Furuq science. Then the author applies the findings of the Furuq usuliyyah principle into the context of Furu' Fiqhiyyah (Fiqh Law). Among the most important achievements produced by the author in this study are: that the science of al-Furuq is the most important discussion, and the benefits are very large in the science of Proposal of Jurisprudence, even in all fields of science. Therefore, the scholars research many of these in their works. From the author's study of the book at-Tahbir Syarh at-Tahrir in the discussion on the law.